An Association of PTPN11 and SHOX Mutations in a Male Presenting With Syndromic Growth Failure - Savarese, Emanuela; Di Felice, Benedetta; Miconi, Francesco; Cabiati, Gabriele; Celi, Federica; Crescenzi, Francesco; Principi, Nicola; Esposito, Susanna (Frontiers in Endocrinology, 2018)
In children with genetic syndromes, short stature is frequently a characteristic feature that, when associated with other specific manifestations, significantly aids in clinical diagnosis. In this report, an atypical case of Noonan syndrome (NS) in a 5.5-year-old child with mesomelic short stature is described. Genetic tests revealed two different mutations in this child. As expected in an NS case, a mutation in PTPN11 gene related to the RAS/MAPK signal transduction pathway was identified. Moreover, a mutation in the SHOX gene that was able to cause disproportionate short stature was detected. A clinical picture of NS with mesomelic short stature makes the diagnosis even more difficult as haploinsufficiency and complete loss of function of SHOX gene are associated with the typical differentiation and proliferation of chondrocytes, leading to mesomelic appearance. This case exemplifies the difficulties that can be encountered in achieving proper diagnoses for children with syndromic diseases and highlights the role of genetic tests in identifying final diagnoses in these patients